2021
DOI: 10.18371/fcaptp.v4i39.241311
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Digitalization on Employment Transformation in Countries With Different Income Levels

Abstract: Abstract. It has been substantiated that digitalization is a driver of the transformation of employment in different countries.The degree of formation of the digitalized labor market by groups of countries with different levels of per capita income has been studied. It is proved that the use of digital technologies by the vast majority of companies and the economically active population simplifies the procedure of job creation, giving the opportunity to work via the Internet within the so-called “on-demand eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…Sustainability extends beyond the economic sector, making its presence felt in various aspects of our society. In the labor market, the growth of new technologies and the rise of self-employment are transforming the way we work [1]. The convergence between sustainable rural development and organic farming presents organic farming as a promising alternative to conventional agriculture [3].…”
Section: Importance Of Sustainability In Today's Worldmentioning
confidence: 99%
“…Sustainability extends beyond the economic sector, making its presence felt in various aspects of our society. In the labor market, the growth of new technologies and the rise of self-employment are transforming the way we work [1]. The convergence between sustainable rural development and organic farming presents organic farming as a promising alternative to conventional agriculture [3].…”
Section: Importance Of Sustainability In Today's Worldmentioning
confidence: 99%
“…Financial inclusion through the usage of an account to save significantly affects stock market participation. Didenko et al [176] show the effect of financial inclusion on the amount of illegally acquired income of countries with different economic developments. Overall, it has been concluded that the level of financial inclusion of the country's population positively affects the fight against money laundering in all countries studied.…”
Section: Financial Literacy and Financial Inclusionmentioning
confidence: 99%